Perlindungan Hukum terhadap Investor dalam Perjanjian Jual Beli Saham Dengan Hak Membeli Kembali (Repurchase Agreement) Yang Diperjualbelikan PT. OSO Securities Cabang Medan - Sandrawati, Erna; Siregar, Mahmul; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The purpose of this study is to find out how the position of the agreement in the sale and purchase of shares with repurchase rights (REPO) in law in Indonesia, whether the sale and purchase agreement of shares with repurchase rights (REPO) has protected the interests of investors, as well as how the settlement of disputes in the sale and purchase agreement shares with repurchase rights (REPO) between issuers and investors by PT. OSO Medan Branch Securities. The method in this research is a normative juridical legal method with qualitative analysis. From the results of the study, it was found that the sale and purchase agreement of shares brokered by PT. OSO Sekuritas is a form of agreement or contract which must comply with the provisions in the Civil Code in general and specifically must comply with the laws and regulations relating to REPO. In the share sale and purchase agreement brokered by PT. OSO Sekuritas has provided legal certainty and protection to investors because in the agreement clause the form of protection has been explained. Settlement of disputes that occur between the parties in the REPO share-purchase agreement brokered by PT. OSO Sekuritas, contained in the agreement clause, which is an agreement for mediation and deliberation as well as resolving issues through the capital market arbitration body, if deliberation is not reached.